TU1.11 Patients' views on laparoscopic cholecystectomy consent process: Consent in clinic improves quality of informed consent and patient satisfaction. (9th August 2022) - Yang, Peiming
Abstract: Aims: Informed consent for elective laparoscopic cholecystectomy should begin at first clinic consultation. Due to clinic time pressures, informed consent is often obtained on the morning of surgery for the first time. This study aims to assess whether consent quality and patients' consent satisfaction are better in clinic compared to day of surgery. Methods: Retrospective review of all elective laparoscopic surgeries between April and June 2021. Self-administered questionnaire was also completed by the same cohort to ascertain consent satisfaction. Results: 38 patients in total during study period. 16(42.1%) were consented in clinic, and 22 were first consented on day of surgery. 25/38(65.8%) patients prefer to be consented in clinic, 13(34.2%) prefer consent on day of surgery. Significantly higher proportion of consent forms from clinic had full documentation of risks and benefits of cholecystectomy (P<0.001) compared to consents from day of surgery. Significantly higher proportion of patients consented in clinic felt adequately informed of procedure, had alternative options explained to them, were informed regarding recovery process, and felt there was adequate time for consent (P<0.05). Insignificantly higher proportion of patients consented in clinic received information leaflet about procedure. Overall consent satisfaction was significantly higher in patients consented in clinic (77% versus 55%, P=0.048%) Conclusions: Consent quality and patient satisfaction levels for elective cholecystectomy were statistically significantly higher when consent was carried out in clinic prior to surgery compared to on the day of surgery. We recommend that all elective cholecystectomy consent is performed formally in clinic prior to surgery.